Development of Android-based Interactive Learning Media to Improve Student Understanding Through Experiments on Optical Equipment Materials - Nur Aini; Dadi Rusdiana (Universitas Lambung Mangkurat, 2024)
Learning media based on the Industrial Revolution 4.0 are required to link learning with technical advancements and dramatically improve the learning experience. This study aims to (1) create a product in the form of Android-based mobile-learning media that can carry out virtual experiments on learning about image creation in mirrors. (2) Assessing the practicality of the learning medium created for conducting experiments. (3) Understanding students' reactions to learning media based on Android. (4) Understanding students' comprehension of experiments utilizing the media generated. This research is development research, or R&D, based on the ADDIE development paradigm. There are five stages: 1) analysis, 2) design, 3) development, 4) implementation, and 5) evaluation. The subjects in this research were 28 class XI Science students. This research design is a one-group pretest-posttest design. Questionnaires and interviews were used to collect data regarding suitability and student responses in this research. The data analysis technique employed in this research uses the statistical Wilcoxon and n-gain tests. The Wilcoxon test results obtained a sign value (0.000) < 0.05, indicating differences in student learning outcomes before and after treatment, and the N-Gain test results showed that 50% of students had high understanding and 32% had moderate understanding. So the research findings reveal the feasibility of using Android-based interactive learning media to boost student knowledge through experiments on optical materials.